A systematic review of the impact of emerging technologies in shaping technical and vocational education and training students’ learning styles - Fatokun, Jonathan Olanrewaju; Gumbo, Mishack Thiza (Educational Challenges, 2025)
The rapid advancement of emerging technologies is fundamentally reshaping Technical and Vocational Education and Training (TVET), driving a transformation in both pedagogical practices and student learning styles. Purpose. This review critically examines the impact of technologies such as Artificial Intelligence (AI), Virtual Reality (VR), Augmented Reality (AR), the Internet of Things (IoT), and digital learning platforms on TVET. Methodology. The study adopted the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) systematic review approach to review relevant articles that explore how emerging technologies facilitate learning in TVET colleges. A literature search was conducted within bibliographic databases to track relevant articles on emerging technologies, TVET, and learning styles. 43 articles that met the final eligibility criteria were subjected to deep review, which yielded the results presented in the study. Results. The study reveals that the integration of these tools enhances hands-on, interactive, and personalized learning experiences, catering to diverse learner preferences and equipping graduates with essential digital skills for the modern workforce. While the adaptation of teaching strategies to individual learning styles remains debated, evidence supports the use of multimodal, technology-enhanced approaches to foster inclusivity and improve educational outcomes. Conclusion. The review identifies gaps between student learning preferences and the evolving technological landscape, offering recommendations for bridging these divides and for the successful integration of emerging technologies in TVET. Ultimately, this study underscores the necessity for ongoing research and strategic implementation to ensure that TVET remains responsive to both learner diversity and industry demands in the 21st century.